Reply to Brent (1998) - Ralph E. Townsend (Journal of Research in Rural Education, 1998)
Brent (1998) has made an important contribution in the development of the nonresidential expanded tax base (ETB) approach to school finance. As Brent indicates, the nonresidential ETB may cut the Gordian knot of achieving both local control and also student equity under property tax funding of local education. He showed that the nonresidential ETB approach can achieve somewhat greater equity in school finance. And his inclusion of a districtlevel behavioral response model, in particular, is an improvement over previous studies. But the paper seriously understates the potential equity gains from a carefully designed nonresidential ETB. The formula for redistribution ofETB revenues is a critical component of the system. Brent fails to examine the kind of equity-generating formulae already in use in some states to distribute general state aid to education. Had Brent examined such formulae, he would have concluded that virtually any equity objective can be achieved by a nonresidential ETB system. When the nonresidential ETB is complemented by similar equity-generating distribution of state aid for education from general revenues, the conclusion is even stronger.